2021
DOI: 10.3390/v13122345
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Methylcellulose-Based Nasal Sprays Effectively Inhibit In Vitro SARS-CoV-2 Infection and Spread

Abstract: The ongoing coronavirus disease (COVID-19) pandemic has required a variety of non-medical interventions to limit the transmission of the causative agent, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). One such option is over-the-counter nasal sprays that aim to block virus entry and transmission within the nasal cavity. In this study, we assessed the ability of three hydroxypropyl methylcellulose (HPMC)-based powder nasal sprays, produced by Nasaleze, to inhibit SARS-CoV-2 infection and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…To date, several in-vitro and animal studies have investigated the use of nasal spray formulations in the post-exposure prophylaxis of SARS-CoV-19 infection 17 , 18 , 19 . A wide range of substances aimed at blocking viral entry to the host have been proposed for nasal administration and are currently being trialled in humans including quinine, nitric oxide, and povidine iodine [20] .…”
Section: Discussionmentioning
confidence: 99%
“…To date, several in-vitro and animal studies have investigated the use of nasal spray formulations in the post-exposure prophylaxis of SARS-CoV-19 infection 17 , 18 , 19 . A wide range of substances aimed at blocking viral entry to the host have been proposed for nasal administration and are currently being trialled in humans including quinine, nitric oxide, and povidine iodine [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Bentley and Stanton investigated the effectiveness of three different hydroxypropyl methylcellulose (HPMC)-based nasal sprays (93% HPMC, 2% peppermint powder and 5% European wild garlic powder; 95% HPMC, 2% peppermint powder and 3% allicin powder; 98.5% HPMC and 1.5% peppermint powder) to prevent in vitro SARS-CoV-2 infection [ 45 ]. Pre-treatment of ACE2-expressing VeroE6 cells with each of these compounds at a concentration of 6.4 mg/3.5 cm 2 was effective to prevent SARS-CoV-2 infection, but was also associated with almost total inhibition of virus release from infected cells.…”
Section: The Role Of Mucosal Protection In Preventing Sars-cov-2 Infe...mentioning
confidence: 99%
“…Similarly, another study identified that Omicron variant replicates more rapidly in the respiratory tract than all other SARS-CoV-2 variants, but less efficiently in the lungs, which may explain the reduced severity of Omicron that is now being reported in epidemiological studies (19). As the highest viral loads are detectable in the upper respiratory tract, reducing infectious viruses in the nasopharynx could lower viral shedding and, consequently, transmission by infected individuals (20).…”
Section: Introductionmentioning
confidence: 98%